Modified waterproof coiled material based on waste high polymer material and preparation method of modified waterproof coiled material
By using waste polymer materials and nanosilicon dioxide and other components in the modified waterproof rolls and adopting specific mixing and extrusion processes, the problem of low bonding performance between the rolls and the base layer is solved, significantly improving the bonding strength and the reliability of the waterproof system.
Patent Information
- Application Number
- CN202411829848.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
AI Technical Summary
The existing modified waterproof coils have low bonding performance when connected to the base layer, which is prone to hollowing and falling off problems, affecting the reliability of the waterproof system.
A modified waterproof coil based on waste polymer materials is used, and a coil with high bond strength is formed by adding waste thermoplastic polyurethane, waste rubber powder, asphalt, nanosilica, silane coupling agent, tackifying resin and antioxidant to the coil, and a specific mixing and extrusion process is used.
It significantly improves the bonding strength between the coil and the base layer, prevents hollowing and falling off, ensures firm bonding under various base layer conditions, and improves the reliability of the waterproof system.
Smart Images

Figure CN119529738A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coiled materials, in particular to a modified waterproof coiled material based on waste polymer materials and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry and the continuous improvement of people's living standards, polymer materials have been widely used in many fields, such as construction, packaging, automobile manufacturing, electronic appliances, etc. However, this has also led to the generation of a large amount of waste polymer materials, and the disposal of these waste materials has become a serious environmental and resource problem.
[0003] At the same time, in the field of building waterproofing, as a key waterproof material, the market demand for waterproofing membranes has always remained at a high level. Traditional waterproofing membranes are usually prepared with petroleum asphalt, SBS (styrene-butadiene-styrene block copolymer), APP (random polypropylene) and other main raw materials. However, these traditional raw materials are facing the problem of increasing resource shortage and large price fluctuations, which to a certain extent limits the further development and application of traditional waterproofing membranes. At the same time, with the continuous enhancement of people's environmental awareness and the deep-rooted concept of sustainable development, the development of new waterproofing membranes based on waste polymer materials has extremely important practical significance. It can not only effectively solve the environmental pollution problem of waste polymer materials and realize the recycling of resources, but also reduce the production cost of waterproofing membranes, improve the market competitiveness of products, and promote the green and sustainable development of the building waterproofing industry.
[0004] The waterproof membrane made of polymer materials has a strong cost-effectiveness in terms of price and also solves the problem of handling a large amount of waste polymer materials. However, during the use of the waterproof membrane, due to material problems, the bonding performance of the membrane is low when connected to the base layer, which leads to problems such as hollowing and falling off during use, seriously affecting the reliability of the waterproof system. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a modified waterproof membrane based on waste polymer materials and a preparation method thereof, which solves the problems that the existing modified waterproof membrane has low adhesion performance with the base layer during use, is prone to hollowing and falling off, and affects the reliability of the waterproof system.
[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a modified waterproof roll based on waste polymer materials, including 40%-50% waste thermoplastic polyurethane, 25%-30% waste rubber powder, 15%-20% asphalt, 5%-7% nano silicon dioxide, 1%-2% silane coupling agent, 3%-5% tackifying resin, and 0.5%-1% antioxidant.
[0007] A method for preparing a modified waterproofing roll based on waste polymer materials comprises the following steps: S1. The waste TPU particles and waste rubber powder are pre-mixed in a high-speed mixer to make them initially evenly dispersed; S2. Heat the asphalt using a heater, and after the asphalt is completely melted, slowly add the asphalt into the mixer and continue stirring until a uniform mixture is formed; S3. Pour the silane coupling agent into the nano-silica and mix them, and use a mixer to mix and stir; S4. The silane coupling agent-modified nano-silica and the tackifying resin are added to the above mixture, and the stirring speed is increased so that the components are fully mixed and interact with each other; S5. Finally, the antioxidant is added and stirred to mix so that the antioxidant is evenly dispersed in the system; S6. The mixed material is extruded through an extruder to obtain a preformed coil, and then the preformed coil is calendered using a calender to make the coil uniform in thickness and smooth in surface; S7. After calendering is completed, the coil is naturally cooled at room temperature until the coil is completely shaped, and finally a modified waterproof coil is produced.
[0008] Preferably, in step S1, the mixing time of the waste TPU particles and the waste rubber powder is 5-10 minutes, and the mixing speed is 800-1000 rpm.
[0009] Preferably, in step S2, the asphalt heating time is 15-20 minutes and the heating temperature is 150-160°C.
[0010] Preferably, in step S2, the asphalt mixing time is 10-15 minutes, and the mixing speed is 600-800 rpm.
[0011] Preferably, in step S3, the mixing time of the silane coupling agent and the nano-silicon dioxide is 10-15 minutes, and the stirring speed is 1000-1200 rpm.
[0012] Preferably, in step S4, the nano-silicon dioxide, tackifying resin and raw materials are mixed at a stirring speed of 1200-1500 rpm for 15-20 minutes.
[0013] Preferably, in step S5, the stirring time of the antioxidant is 3-5 minutes, and the stirring speed is 800-1000 rpm.
[0014] Preferably, in step S6, the calendering time of the calender is 3-5 minutes, and the calendering pressure is controlled at 5-8 MPa.
[0015] Preferably, in step S7, the room temperature is specifically 20-25° C., and the cooling time is 10-15 minutes.
[0016] The present invention provides a modified waterproofing roll material based on waste polymer materials and a preparation method thereof, which has the following beneficial effects: 1. The present invention utilizes waste polymer materials to make modified waterproof membranes. After nano-silicon dioxide is modified by a silane coupling agent, it forms a chemical bond or strong physical adsorption with the surface of the base layer, which significantly improves the interfacial bonding strength. At the same time, the addition of a tackifying resin further enhances the overall viscosity of the membrane, ensuring that it can be firmly bonded under various base conditions and effectively preventing hollowing and falling off.
[0017] 2. The present invention makes full use of waste polymer materials, realizes the recycling of resources, reduces dependence on increasingly scarce raw materials such as traditional petroleum asphalt, SBS, APP, etc., reduces production costs, and improves product market competitiveness. At the same time, it helps to alleviate the pressure on the environment caused by waste polymer materials, conforms to the concept of sustainable development, and has positive significance for promoting the green transformation of the building waterproofing industry.
[0018] 3. The present invention is provided with a plurality of different embodiments, each with its own unique advantages. Embodiment 1 improves adhesion by combining waste materials, and is suitable for coping with daily situations such as uneven base layers; Embodiment 2 enhances low-temperature performance by adding ingredients, and can be used in high-cold areas; Embodiment 3 has good moisture resistance due to the aqueous polyurethane dispersion, and is suitable for humid environments; Embodiment 4 uses nano-calcium carbonate to enhance hardness and wear resistance, and is suitable for places susceptible to friction. The overall embodiment provides a high-performance solution that is adaptable to multiple scenarios for building waterproofing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Embodiment 1: Please refer to the attached Figure 1 The embodiment of the present invention provides a modified waterproof membrane based on waste polymer materials, including 40%-50% of waste thermoplastic polyurethane, 25%-30% of waste rubber powder, 15%-20% of asphalt, 5%-7% of nano silicon dioxide, 1%-2% of silane coupling agent, 3%-5% of tackifying resin, and 0.5%-1% of antioxidant.
[0022] A method for preparing a modified waterproofing roll based on waste polymer materials comprises the following steps: S1. The waste TPU particles and waste rubber powder are pre-mixed in a high-speed mixer for 5-10 minutes, and the mixer speed is set to 800-1000 rpm to make it initially evenly dispersed; S2. Heat the asphalt using a heater for 15-20 minutes at a temperature of 150-160°C, and after the asphalt is completely melted, slowly add the asphalt to the mixer and continue stirring for 10-15 minutes at a stirring speed of 600-800 rpm until a uniform mixture is formed; S3. The silane coupling agent is poured into the nano-silica and mixed, and mixed using a stirrer, the stirring time is 10-15 minutes, and the stirring speed is 1000-1200 rpm; S4. The silane coupling agent-modified nano-silica and tackifying resin are added to the above mixture, the stirring speed is increased to 1200-1500 rpm, and stirred for 15-20 minutes to allow the ingredients to be fully mixed and interact with each other; S5. Finally, add the antioxidant and stir for 3-5 minutes at a stirring speed of 800-1000 rpm to uniformly disperse the antioxidant in the system; S6. The mixed material is extruded through an extruder to obtain a preformed coil, and then the preformed coil is calendered using a calender, the calendering time is 3-5 minutes, and the calendering pressure is controlled at 5-8MPa, so that the coil thickness is uniform and the surface is smooth; S7. After calendering, the coil is naturally cooled at room temperature of 20-25°C for 10-15 minutes until the coil is completely shaped and finally made into a modified waterproof coil.
[0023] Beneficial effects of Example 1: This example uses waste TPU particles and waste rubber powder to provide the coil with good flexibility and elasticity, so that it can adapt to the slight deformation of the base layer and reduce the risk of separation between the coil and the base layer due to changes in the base layer. At the same time, after the nano-silicon dioxide is modified with a silane coupling agent, the surface active groups are greatly increased. When the coil contacts the base layer, it can form a chemical bond or strong physical adsorption with the surface material of the base layer, significantly improving the interfacial bonding strength, forming a stable bonding interface, and effectively solving the problem of poor bonding with the base layer.
[0024] Embodiment 2: A modified waterproofing membrane based on waste polymer materials, including 40% waste thermoplastic polyurethane, 25% waste rubber powder, 15% asphalt, 5% nano-silicon dioxide, 1% silane coupling agent, 3% tackifying resin, 0.5% antioxidant, 5% ethylene-vinyl acetate copolymer, 3% maleic anhydride grafted polypropylene, and 2% polyamide wax powder.
[0025] Embodiment 2 Beneficial Effect: In this embodiment, the added EVA further enhances the flexibility and low-temperature performance of the coiled material, so that it can still maintain good adhesion and waterproof properties in a low-temperature environment, effectively expanding the application scope of the coiled material.
[0026] Embodiment 3: A modified waterproofing membrane based on waste polymer materials, including 42% waste thermoplastic polyurethane, 26% waste rubber powder, 16% asphalt, 6% nano-silicon dioxide, 1.5% silane coupling agent, 4% tackifying resin, 0.8% antioxidant, 3% water-based polyurethane dispersion, 2% organic bentonite, and 1% dioctyl ester.
[0027] Beneficial effect of Example 3: This example not only increases the environmental friendliness of the coiled material by adding an aqueous polyurethane dispersion, but also gives the coiled material better water resistance and bonding durability. In a long-term humid environment, the decrease in its bonding strength with the base layer is reduced by about 30% compared with Example 1.
[0028] Embodiment 4: A modified waterproofing membrane based on waste polymer materials, including 45% waste thermoplastic polyurethane, 28% waste rubber powder, 18% asphalt, 7% nano silicon dioxide, 2% silane coupling agent, 5% tackifying resin, 1% antioxidant, 3% nano calcium carbonate, 2% terpene phenolic resin, and 1% epoxy soybean oil.
[0029] Beneficial effects of Example 4: This example enhances the hardness and wear resistance of the coil by adding nano calcium carbonate, and can better maintain the structural integrity when the coil is subjected to external friction or extrusion. At the same time, it synergizes with the silane coupling agent to further enhance the chemical bonding force with the base layer, thereby increasing the bonding strength by about 25% compared with Example 1.
[0030] Comparative experiment: 1. Adsorption effect comparison experiment Experimental design: Five samples of the modified waterproof membranes of Example 1, Example 2, Example 3, and Example 4 of the same size (10 cm×10 cm) were prepared.
[0031] To make a simulated base board, evenly apply a thin layer of simulated pollutant (a mixture of fine sand, dust and a small amount of grease) on the smooth surface of the cement board.
[0032] Each coil sample was placed tightly on the simulated base plate and rolled back and forth three times using a 5kg standard pressure roller to ensure full contact.
[0033] After being placed in an environment with a temperature of 25°C and a relative humidity of 60% for 24 hours, a high-precision electronic balance was used to measure the weight increase of the coil after adsorbing pollutants to evaluate the adsorption effect.
[0034] Experimental results: The average weight increase of the coiled material sample of Example 1 is 0.85g, and the adsorption effect is the best among the four groups of samples. The good flexibility provided by the waste TPU particles and waste rubber powder enables the coiled material to fit the surface of the base layer more closely, and the enhanced interfacial adhesion of the silane coupling agent-modified nano-silica helps to adsorb the pollutant particles on the surface of the base layer, showing a strong adsorption capacity.
[0035] The average weight increase of the coiled material sample of Example 2 is 0.62 g. Although the addition of EVA and other ingredients enhances flexibility and low-temperature performance, the improvement in adsorption effect is not as good as that of Example 1.
[0036] The average weight increase of the coiled material sample of Example 3 is 0.58 g. The components such as the waterborne polyurethane dispersion mainly improve the water resistance and environmental protection, and contribute relatively little to the ability to adsorb pollutants.
[0037] The average weight increase of the coiled material sample of Example 4 is 0.55 g. Ingredients such as nano calcium carbonate focus on enhancing hardness and wear resistance, and have limited effect on improving the adsorption effect.
[0038] 2. Comparative experiment on anti-low temperature effect Experimental design: Take 3 sections of coil samples of each embodiment with the same specifications (length 20 cm, width 5 cm, thickness 3 mm).
[0039] The samples were placed in a low temperature test chamber and treated at -20°C for 48 hours.
[0040] After taking out, immediately conduct a bending test on a universal material testing machine to measure the bending stress of the sample when it is bent to 90 degrees at low temperature, and observe whether there are cracks. The greater the bending stress and the absence of cracks, the better the low temperature resistance.
[0041] Experimental results: The average bending stress of the coil sample of Example 2 when bent to 90 degrees at -20°C is 12.5MPa, and no cracks are generated, with the best low temperature resistance. This is due to the fact that the added EVA component effectively improves the flexibility and adhesion of the coil in a low temperature environment, enabling it to withstand large bending deformation without damage.
[0042] The average bending stress of the coil sample of Example 1 is 10.2 MPa, and slight cracks appear. Its low temperature resistance is relatively weak, and although the waste TPU particles and waste rubber powder provide a certain basis, it does not perform as well as Example 2 at extremely low temperatures.
[0043] The average bending stress of the coil sample of Example 3 is 9.8 MPa, and many fine cracks appear. The improvement of low temperature performance by components such as waterborne polyurethane dispersion is limited.
[0044] The average bending stress of the coil sample of Example 4 is 9.5 MPa, and the cracks are relatively obvious. Ingredients such as nano calcium carbonate focus on hardness and wear resistance, and do not play a significant role in improving low temperature resistance.
[0045] 3. Moisture resistance comparison test Experimental design: Four test pieces of the coiled material of each embodiment of the present invention were prepared with the same size (15 cm×15 cm).
[0046] The specimens were immersed in simulated groundwater at a temperature of 30°C and a pH value of 7. A group of specimens were taken out every 7 days. The adhesion between the membrane and the simulated base layer (standard concrete slab) was tested using a professional adhesion tester, and the adhesion retention rate (the ratio of the adhesion after immersion to the initial adhesion) was calculated.
[0047] Experimental results: After immersion for 28 days, the average adhesion retention rate of the coiled material specimens of Example 3 was 85%, and the moisture resistance performance was the best. The addition of the waterborne polyurethane dispersion significantly improved the adhesion durability of the coiled material in a long-term humid environment, and the decrease in its adhesion to the base layer was reduced by about 30% compared with Example 1, effectively ensuring the waterproof effect under humid conditions.
[0048] After the same immersion time, the average adhesion retention rate of the coiled material specimens of Example 1 was 65%. Although it has a certain moisture resistance, compared with Example 3, the adhesion decreases significantly in a long-term humid environment.
[0049] The average adhesion retention rate of the coiled material specimens of Example 2 is 62%. EVA and other ingredients mainly enhance flexibility and low temperature performance, and have little effect on improving moisture resistance.
[0050] The average adhesion retention rate of the coiled material specimens of Example 4 is 60%. The improvement of moisture resistance by components such as nano-calcium carbonate is relatively small, and the focus is on hardness and wear resistance.
[0051] 4. Hardness and wear resistance comparison test Experimental design: Three samples of the coil discs of each embodiment with the same size (10 cm in diameter and 2 cm in thickness) were used.
[0052] The sample was fixed on an abrasion tester, and a rubber grinding wheel with a standard hardness of 80 Shore A was used to perform a wear test on the sample surface at a load of 500 g and a speed of 100 revolutions per minute for 30 minutes.
[0053] After the test, the wear depth of the sample surface is measured using a surface roughness meter. The smaller the wear depth, the better the hardness and wear resistance.
[0054] Experimental results: The average wear depth of the coil sample of Example 4 is 0.12mm, and the hardness and wear resistance are the strongest. The addition of nano calcium carbonate effectively enhances the hardness of the coil, making it better able to resist wear when subjected to external friction, and synergistically with the silane coupling agent, further improving the wear resistance while maintaining the structural integrity.
[0055] The average wear depth of the coil sample of Example 1 is 0.25 mm. Its hardness and wear resistance are relatively weak, mainly relying on the performance of the base material, and have not been optimized specifically for hardness and wear resistance.
[0056] The average wear depth of the coil sample of Example 2 is 0.28 mm. Ingredients such as EVA focus on flexibility and low temperature performance, and have limited improvement on hardness and wear resistance.
[0057] The average wear depth of the coiled material sample of Example 3 is 0.30 mm. The components such as the waterborne polyurethane dispersion mainly improve water resistance and environmental protection, and have a small contribution to hardness and wear resistance.
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A modified waterproofing membrane based on waste polymer materials, characterized in that: Including 40%-50% waste thermoplastic polyurethane, 25%-30% waste rubber powder, 15%-20% asphalt, 5%-7% nano silicon dioxide, 1%-2% silane coupling agent, 3%-5% tackifying resin, and 0.5%-1% antioxidant.
2. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 1, characterized in that: The following steps are involved: S1. The waste TPU particles and waste rubber powder are pre-mixed in a high-speed mixer to make them initially evenly dispersed; S2. Heat the asphalt using a heater, and after the asphalt is completely melted, slowly add the asphalt into the mixer and continue stirring until a uniform mixture is formed; S3. Pour the silane coupling agent into the nano-silica and mix, and use a mixer to mix and stir; S4. The silane coupling agent-modified nano-silica and the tackifying resin are added to the above mixture, and the stirring speed is increased so that the components are fully mixed and interact with each other; S5. Finally, the antioxidant is added and stirred to mix so that the antioxidant is evenly dispersed in the system; S6. The mixed material is extruded through an extruder to obtain a preformed coil, and then the preformed coil is calendered using a calender to make the coil uniform in thickness and smooth in surface; S7. After calendering is completed, the coil is naturally cooled at room temperature until the coil is completely shaped, and finally a modified waterproof coil is produced.
3. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In the step S1, the waste TPU particles and the waste rubber powder are mixed for 5-10 minutes at a mixing speed of 800-1000 rpm.
4. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In step S2, the asphalt is heated for 15-20 minutes at a temperature of 150-160°C.
5. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In step S2, the asphalt mixing time is 10-15 minutes, and the mixing speed is 600-800 rpm.
6. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In step S3, the silane coupling agent and nano-silicon dioxide are mixed and stirred for 10-15 minutes at a stirring speed of 1000-1200 rpm.
7. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In the step S4, the nano-silicon dioxide, tackifying resin and raw materials are mixed at a stirring speed of 1200-1500 rpm for 15-20 minutes.
8. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In step S5, the stirring time of the antioxidant is 3-5 minutes, and the stirring speed is 800-1000 rpm.
9. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In step S6, the calendering time of the calender is 3-5 minutes, and the calendering pressure is controlled at 5-8 MPa.
10. The method for preparing a modified waterproofing roll based on waste polymer materials according to claim 2, characterized in that: In step S7, the room temperature is specifically 20-25° C., and the cooling time is 10-15 minutes.
Citation Information
Cited By
Waste thermoplastic polyurethane modified asphalt and preparation method thereof
CN120025695A